"Respeta mi idioma": Latinx Youth Enacting Affective Agency. Issue 2 (3rd March 2020) - Ferrada, Juan Sebastián; Bucholtz, Mary; Corella, Meghan
ABSTRACT: Although hegemonic approaches to education privilege rationality as the sole legitimate form of knowledge production and consumption, research on emotion in socially transformative learning demonstrates that it is only through affective investment that intellectual engagement takes place and leads to social change. Hence, the agentive action of racialized youth to produce knowledge challenging dominant ideological systems is also an affective agency, the production of social action informed by and involving embodied, emotional encounter with the world. The article identifies three key components of affective agency—affective encounter, mobilization, and persistence—through ethnographic interactional analysis in an innovative after-school program for Latinx youth. The analysis examines one student's emotional response to linguistic racism in U.S. political discourse and how this affective experience moved her to speak out for sociolinguistic justice for Spanish speakers. The article concludes that educators committed to antiracism and social justice must interactionally support students' affective agency.